2021
DOI: 10.1080/01140671.2020.1861032
|View full text |Cite
|
Sign up to set email alerts
|

Pollination requirements of kiwifruit (Actinidia chinensis Planch.) differ between cultivars ‘Hayward’ and ‘Zesy002’

Abstract: Pollination by insects is critical for the production of many crops worldwide. Crop cultivars vary in a number of traits, but their differing pollination requirements are often overlooked. Kiwifruit (Actinidia chinensis) is reliant on pollen movement between male and female plants, but there has been disagreement in the literature about what its pollination requirements are. Additionally, there is little information about how time-of-day might affect fruit and seed set, and how this may alter the efficacy of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…As kiwifruit can produce fruit regardless of the time-of-day pollination occurs ( Broussard et al, 2021 ), pollination need not be limited to peak honey bee foraging hours (late morning to early afternoon). There is the potential for other pollination strategies to compliment managed honey bees, including alternative insect pollinators and artificial pollination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As kiwifruit can produce fruit regardless of the time-of-day pollination occurs ( Broussard et al, 2021 ), pollination need not be limited to peak honey bee foraging hours (late morning to early afternoon). There is the potential for other pollination strategies to compliment managed honey bees, including alternative insect pollinators and artificial pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that gold-fleshed kiwifruit appear to have a lower pollination requirement than green kiwifruit ( Broussard et al, 2021 ), with green-fleshed ‘Hayward’ requiring 8x the insect visits of yellow-fleshed varieties ‘Hort16A’ and ‘Zesy002’ ( Broussard et al, 2021 ). This means that non- Apis pollinators, even those who deposit less pollen per visit, may have a greater part to play in these cultivars, as the number of grains they do deposit represents a larger percentage of the overall requirement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third option is available for selected, self-compatible crops-such as tomato-where vibrating the floral structures, either through direct contact or with a puff of air, shakes loose pollen to fertilize the flower [59]. Most application literature measures results directly in terms of fruit or seed set, as pollen requirements have been characterized for relatively few crops [60][61][62][63]. Research has shown that liquid-carrier (or dry diluent composition) formulation, temperature, time of day, weather, stigma receptivity, and flower age all influence pollination efficacy [41,61,[64][65][66][67][68].…”
Section: Pollen Applicationmentioning
confidence: 99%
“…Dry application has two important advantages over wet pollen application: Most application literature measures results directly in terms of fruit or seed set, as pollen requirements have been characterized for relatively few crops [60][61][62][63]. Research has shown that liquid-carrier (or dry diluent composition) formulation, temperature, time of day, weather, stigma receptivity, and flower age all influence pollination efficacy [41,61,[64][65][66][67][68]. These factors are largely ignored in much of the work published on alternative pollination systems.…”
Section: Pollen Applicationmentioning
confidence: 99%